Draft Annual Plan 1988-89 Volume : III General Areas Government of Assam - (:unkn) unknown (Planning Commission, 1987)
The annual energy generation is estimated to be 401 million units in 90 percent year and 466 million units in average year. The latest revised cost estimate based on the tenders etc. has now amounted to Rs. 87.51 crores. The cost of generation is estimated to be 23 paisa per unit. As per the revised Pert and discussions held with the Central Electricity Authority in May 86, the target for commissioning, of first unit is March 89 and. Second unit by Sept 89. However, due to cancellation of due contract for .dam the works of dam remained suspended since March 87 and likely to. resume from next working season. As per the latest review, the first unit is expected to be commissioned by December and. the second unit-6 month there after.
Government of Assam
Planning and Development Department
Keywords: Power Generation; Programme Under Inspectorate of Electricity; Non Conventional Sources of Energy; Village & Small Industries; Handloom & Powerloom; Sericulture; Khadi Village Industries; Industries (other than village & Small Industries); Geology and Minerals; Weights & Measures; Review of Annual Plan; Industry And Minerals